Barcode DNA high‐resolution melting (Bar‐HRM) analysis as a novel close‐tubed and accurate tool for olive oil forensic use. (11th February 2013) - Ganopoulos, Ioannis; Bazakos, Christos; Madesis, Panagiotis; Kalaitzis, Panagiotis; Tsaftaris, Athanasios
Abstract BACKGROUND The adulteration of high‐priced olive oil with low‐cost oils and the fraudulent labelling of oil products make the identification and traceability of vegetable oil species in the food chain very important. This paper describes a high‐resolution melting analysis‐based method using chloroplast barcoding regions as target (Bar‐HRM) to obtain barcoding information for the major vegetable oil species and to quantitatively identify the botanical origin of plant oils. The detection of adulteration of olive oil with canola oil was used as a case study. RESULTS The proposed method was capable of distinguishing among different vegetable oil species and detecting a level of 1% (w/w) of canola oil in olive oil. CONCLUSION Bar‐HRM analysis is a more accurate, faster and less costly alternative method to authenticate vegetable oils, including olive oil, and to detect mixtures of oils. © 2013 Society of Chemical Industry